Different media affect the growth and antimicrobial minimum inhibitory concentrations of Mycoplasma gallisepticum and Mycoplasma synoviae - Taiyari, Hossein; Abu, Jalila; Zakaria, Zunita; Omar, Sharina; Wen, Chan Zi; Nik Mohd Azmi, Nik Mohd Faiz (Elsevier B.V., 2025)
The main pathogenic Mycoplasma spp. infecting chickens are Mycoplasma gallisepticum (MG) and Mycoplasma synoviae (MS). The MG and MS play an etiological role in chronic respiratory disease. One of the methods to control avian mycoplasmosis is antibiotic therapy. The microdilution minimum inhibitory concentration (MIC) assay is one of the most commonly used tests to assess the antibiotic susceptibility profile of isolates. The effect of type of medium used in the MIC assay of MG and MS has not been evaluated. Therefore, the aim of this study is to determine the impact of two commonly used avian mycoplasmas growth media, Frey medium and Pleuropneumonia-like Organisms (PPLO) medium, on growth rate and the MIC values of MG and MS. The comparison of growth rates and MIC values between two media was conducted in three replicates, and the mean values were used for any further analysis. First, the growth rates of MG and MS were compared in both Frey and PPLO media. Then, antimicrobial MIC values were determined using the microbroth dilution method. The results show that MG and MS isolates had faster growth rates in Frey compared to PPLO (p ≤ 0.05). The antimicrobial MIC values of MG and MS isolates were different in Frey and PPLO media. This study indicates the significant effect of the type of medium used in the determination of antimicrobial MIC values of MG and MS, and can be used as a fundamental source for preparation of a more comprehensive MG and MS MIC protocol.